2021
DOI: 10.1055/a-1385-8863
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects Induced by Fruit Peels from Passiflora edulis in Hypertensive Rats and Fingerprint Analysis by HPLC-ESI-MSn spectrometry

Abstract: Hypertension is a chronic disease and a global health problem. Due to its high prevalence, it constitutes the most important risk factor for cardiovascular disease. Fruit peels from Passiflora edulis fo. flavicarpa are rich in bioactive natural compounds that may have action in hypertension. This study aimed to perform a fingerprinting analysis of Passiflora edulis fruit peel extract and evaluate its actions on the cardiovascular system in an in vivo model. The extract was obtained from the dried and powdered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Although the primary mechanism through which AFA extract can afford nephroprotection in diabetes remains unknown, previous studies performed by partner research groups have demonstrated the adjuvant effect of P. edulis fruit peel extracts in terms of glycemic control in diabetic rats 14,15 . These previous studies have suggested that polysaccharides, such as pectin and flavonoids (orientin and isoorientin), are associated with the hypoglycemic effect of the extract and, consequently, prevent the emergence of diabetes complications 14,15 . Additionally, studies have revealed that pectin and other soluble fibers present in the extract can create a layer of gel-like substances in the stomach, delaying the absorption of food and reducing serum glucose 35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the primary mechanism through which AFA extract can afford nephroprotection in diabetes remains unknown, previous studies performed by partner research groups have demonstrated the adjuvant effect of P. edulis fruit peel extracts in terms of glycemic control in diabetic rats 14,15 . These previous studies have suggested that polysaccharides, such as pectin and flavonoids (orientin and isoorientin), are associated with the hypoglycemic effect of the extract and, consequently, prevent the emergence of diabetes complications 14,15 . Additionally, studies have revealed that pectin and other soluble fibers present in the extract can create a layer of gel-like substances in the stomach, delaying the absorption of food and reducing serum glucose 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of the AFA extract. The AFA extract was obtained and characterized as described by Cabral et al 15 . Briefly, seeds and pulp were removed, and peels were dried in an air circulation oven (55 °C) for two days and mechanically triturated to obtain a dry powder (flour) 15 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been evaluated in animal studies for its safety when administered [19]. P. edulis peel is rich in dietary fiber and functional components, and various physiological effects of P. edulis peel extract have been reported, such as antihypotensive effects [20], hypoglycemic effects [21,22], and metabolic improvement [23,24]. Furthermore, P. edulis bark reportedly has anti-obesity properties [25].…”
Section: Introductionmentioning
confidence: 99%